The THE CORRELATIONS BETWEEN FAMILY ASSISTANCE AND URIC ACID LEVELS IN PATIENTS WITH GOUT ARTHRITIS IN THE ELDERLYAT: hubungan antara pendampingan keluarga dengan penurunan kadar asam urat penderita gout arthritis pada lansia - Susanti, Novia; Atmaja, Bayu Purnama; Pratiwi, Tiara Fatma (LPPM STIKes Bahrul Ulum Jombang, 2022)
The prevalence of gout in Indonesia is increasing, especially in the elderly, then there is a need for family assistance to help the healing process of the disease experienced by the elderly. This study was cross sectional design. The number of samples in this study were 38 respondents with a total sampling technique. The independent variable was family assistance, the dependent variable was the decrease in uric acid levels in patients with gout arthritis in the elderly. The instrument was a questionnaire and observation sheets. The analysis used spearman rank. The results of statistical tests by using the Spearman rank test obtained a sig value (p = 0.002) with a 95% confidence level (ɑ = 0.05) thus it can be said that p = 0.002 < 0.05, then H0 was rejected and H1 was accepted. Thus, it can be concluded that there was a correlations between family assistance and decreased uric acid levels in patients with gout arthritis in the elderly at Desa Rejosari in Kecamatan Mantewe, Tanah Bumbu in 2022. From the results of this study, it was expected that families can provide support and motivation to prevent uric acid levels suffered by elderly.